2015
DOI: 10.1103/physrevlett.115.265702
|View full text |Cite
|
Sign up to set email alerts
|

Negative Pressure Vitrification of the Isochorically Confined Liquid in Nanopores

Abstract: Dielectric relaxation studies for model glass-forming liquids confined to nanoporous alumina matrices were examined together with high-pressure results. For confined liquids which show the deviation from bulk dynamics upon approaching the glass transition (the change from the Vogel-Fulcher-Tammann to the Arrhenius law), we have observed a striking agreement between the temperature dependence of the α-relaxation time in the Arrhenius-like region and the isochoric relaxation times extrapolated from the positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
95
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(110 citation statements)
references
References 41 publications
14
95
1
Order By: Relevance
“… 45 Likewise, the much different behavior of low-molecular-weight liquids glycerol (35 K/GPa) and salol (204 K/GPa) confined in alumina templates was explained in terms of the different contribution of volume and thermal effects in controlling their glassy dynamics. 33 In line with this, the relatively weak sensitivity of P2VP to pressure/density effects might be the origin of its bulk-like behavior in AAO nanopores. One can also use the same type of argumentation for 1,4- cis -polyisoprene ( dT g / dP = 178 K/GPa), 95 in which glass transition temperature was unaffected by 2D confinement, whereas, at the same time, a remarkable broadening of the distribution of relaxation times for both the segmental and chain modes was observed.…”
Section: Resultsmentioning
confidence: 69%
“… 45 Likewise, the much different behavior of low-molecular-weight liquids glycerol (35 K/GPa) and salol (204 K/GPa) confined in alumina templates was explained in terms of the different contribution of volume and thermal effects in controlling their glassy dynamics. 33 In line with this, the relatively weak sensitivity of P2VP to pressure/density effects might be the origin of its bulk-like behavior in AAO nanopores. One can also use the same type of argumentation for 1,4- cis -polyisoprene ( dT g / dP = 178 K/GPa), 95 in which glass transition temperature was unaffected by 2D confinement, whereas, at the same time, a remarkable broadening of the distribution of relaxation times for both the segmental and chain modes was observed.…”
Section: Resultsmentioning
confidence: 69%
“…It is well-established that the dynamics of the liquids conned to nanometer pores is much different from that in the bulk state. [29][30][31][32][33][34][35] In the presence of nanoscale connement, it has been observed that on cooling the temperature dependence of the structural relaxation time starts to depart from the bulk-behavior. This happens as due to verication of the interfacial layer, that is the fraction of molecules located in close proximity of the pore walls.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, to do that we use the same value of the scaling exponent g as that found for substances measured in the bulk. [29][30][31] What remains unclear, however, is whether the idea of the density scaling works in conned geometry for these glass-forming systems which for sure, does not scale in bulk supercooled liquid state.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several experimental studies have been performed to understand the constant volume vitrification [32][33][34][35][36][37][38][39]. The works include experimental studies of glass transition taking place in confined environments.…”
Section: Introductionmentioning
confidence: 99%